Semantic Changes and the Social Media Images in Twitter Gaming Community’s Slangs - Lovely Queen Vidinta Lucentius; Nurina Azyyati; Aisah Aisah (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2026)
Language in digital spaces evolves rapidly, resulting in various changes, including semantic changes. This study examines slangs in the Twitter Gaming Community, a group particularly prone to language change, focusing on patterns of semantic change and identifying the dominant types of semantic change. Such changes can also reflect the community’s social identity. Using Luján's (2010) framework, which includes amelioration, pejoration, metaphorical extension, broadening, and narrowing, this study found that pejoration was the most dominant pattern (35.7%). This indicates a change toward evaluative and competitive discourse. These pejorative pattern changes suggest a linguistic culture shaped by hierarchy, performance, and judgment. Overall, the findings show that slangs in Twitter gaming community demonstrates not only semantic flexibility but also reflect the social dynamics, values, and identity of the gaming subculture within the broader digital media context.Keywords: Semantic Change; Slang; Twitter; Gaming Community; Pejoration; Luján Theory